Effect of erbium, chromium-doped: yttrium, scandium, gallium, and garnet and erbium: yttrium-aluminum-garnet laser etching on enamel demineralization and shear bond strength of orthodontic brackets - Vahid Mollabashi; Loghman Rezaei-Soufi; Maryam Farhadian; Ali Reza Noorani (Wolters Kluwer Medknow Publications, 2019)
Objective: The objective of this study was to compare the effect of two types of laser irradiation (erbium, chromium-doped: yttrium, scandium, gallium, and garnet [Er,Cr:YSGG] and erbium: yttrium-aluminum-garnet [Er:YAG]) and acid etching on enamel demineralization and shear bond strength (SBS) of orthodontic bracketsastry. Materials and Methods: Ninety premolars were selected, scaled, and polished with no fluoridated pumice, and metal brackets were bonded to them. Then, they were randomly allocated to three groups based on the etching procedure: phosphoric acid etching, Er:YAG (100 mJ, 10 Hz) laser etching, and Er,Cr:YSGG (600 mJ, 20 Hz) laser etching. Teeth to be evaluated for demineralization and SBS were exposed to pH and thermal cycling, respectively. For SBS test, a universal testing machine was used, and adhesive remnant was index scored after debonding. Microhardness of enamel was evaluated with Vickers test. Data were analyzed statistically (α = 0.05). Results: The acid-etched group exhibited significantly higher SBS values compared to the laser groups (P < 0.05); however, the difference between the Er:YAG and Er,Cr:YSGG laser groups was not significant. Microhardness mean values in descending order were as follows: Er,Cr:YSGG, Er:YAG, and acid etched. There were significant differences between the laser and control groups (P < 0.001); however, the difference between the two laser groups was not significant (P = 0.320). There were no significant differences between the three groups in adhesive remnant index scores. Conclusion: Er:YAG and Er,Cr:YSGG laser etching resulted in clinically acceptable SBS; therefore, apart from its other advantages over acid etching, it can be a good appropriate alternative for bonding of orthodontic brackets.